Analysis of Healthcare Professionals’ Professionalism in the Pediatric Inpatient Ward at Lahat Regional General Hospital, Lahat Regency, South Sumatra - Mega Sakinah; Rotua Sumihar Sitorus; Sri Melda Br. Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Healthcare professionalism is a fundamental foundation in improving service quality and patient safety in hospitals. This study aimed to analyze the influence of skills, responsibility, ethics, and communication on the professionalism of healthcare workers in the Pediatric Inpatient Unit of Lahat Regional General Hospital, Lahat Regency, South Sumatra, in 2025. This research employed an analytic quantitative design with a cross-sectional approach. The population consisted of 82 healthcare workers, with a sample of 68 respondents selected using stratified random sampling technique. Data were collected using structured questionnaires and analyzed through univariate, bivariate (Chi-Square test), and multivariate (multiple logistic regression) analyses.The results showed that the majority of respondents were categorized as professional (70.6%). Bivariate analysis indicated that skills (p = 0.001), responsibility (p = 0.000), ethics (p = 0.000), and communication (p = 0.018) had a significant influence on professionalism. Multivariate analysis revealed that ethics was the most dominant variable affecting professionalism (OR = 7.25; p = 0.004), followed by responsibility (OR = 5.59; p = 0.009) and skills (OR = 4.26; p = 0.021), while communication was not statistically significant after being controlled with other variables (p = 0.078).In conclusion, ethics, responsibility, and skills are the main factors influencing healthcare professionalism. Enhancing professional ethics training, strengthening responsibility, and continuously developing clinical skills are necessary to improve the quality of healthcare services at Lahat Regional General Hospital.